Design and Development of a tomato Slicing Machine - Salaudeen, Kamaldeen Oladimeji; E. F., Awagu (International Journal of Engineering and Technology, 2012)
Principle of slicing was reviewed and tomato slicing machine was developed based on appropriate technology. Locally available materials like wood, stainless steel and mild steel were used in the fabrication. The machine was made to cut tomatoes in 2cm thickness. The capacity of the machine is 540.09g per minute and its performance efficiency is 70%.